Metastatic Hepatocellular Carcinoma in a Patient with Crohn’s Disease Treated with Azathioprine and Infliximab: A Case Report and Literature Review - Kyle J. Fortinsky; Ali Alali; Khursheed Jeejeebhoy; Sandra Fischer; Morris Sherman; Scott Fung (Case Reports in Gastrointestinal Medicine)
Hepatocellular carcinoma most commonly occurs in patients with underlying liver disease or cirrhosis. We describe a case of hepatocellular carcinoma in a 34-year-old man with Crohn’s disease treated with azathioprine and infliximab. The patient had no history of liver disease and a complete autoimmune and viral workup was unremarkable. Unfortunately, the patient developed widespread metastatic disease and passed away 5 months after his initial diagnosis. The mechanism of hepatocellular carcinoma in patients’ with Crohn’s disease is poorly understood and may include both autoimmunity and treatment-related complications. Previous case reports suggest the possibility of a concerning association between azathioprine therapy and the development of hepatocellular carcinoma in patients with Crohn’s disease. Clinicians may consider early imaging in patients with Crohn’s disease presenting with concerning symptomatology or abnormal liver enzymes, especially in those being treated with azathioprine alone or in combination with infliximab. Future research may help to uncover additional risk factors for this exceedingly rare diagnosis in this patient population.